2011
DOI: 10.1017/s0033291711001814
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal predictors of past-year non-suicidal self-injury and motives among college students

Abstract: Background Non-suicidal self-injury (NSSI) is the deliberate and direct injuring of body tissue without suicidal intent for purposes not socially sanctioned. Few studies have examined the correlates of NSSI among young adults. This paper aimed to identify predictors of lifetime and past-year NSSI; describe motives for NSSI and disclosure of NSSI to others. Method Interviews were conducted annually with 1,081 students enrolled in the College Life Study, a prospective longitudinal study conducted at one large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
3
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 43 publications
10
94
3
6
Order By: Relevance
“…Psychological distress, rather than only internalizing symptoms as reported by several studies (e.g., Guerry et al, 2010;Hankin et al, 2011;Wilcox et al, 2012), is a significant predictor of NSSI, even after statistically controlling for NSSI at time 1, gender, and psychiatric disorder at time 1.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Psychological distress, rather than only internalizing symptoms as reported by several studies (e.g., Guerry et al, 2010;Hankin et al, 2011;Wilcox et al, 2012), is a significant predictor of NSSI, even after statistically controlling for NSSI at time 1, gender, and psychiatric disorder at time 1.…”
Section: Discussionmentioning
confidence: 72%
“…The present study is the first study to examine the role of both internalizing and externalizing symptoms, conceptualized as psychological distress, in a longitudinal design. Previous research has established that internalizing symptoms (e.g., depressive symptoms) contribute to the occurrence of NSSI in two-wave longitudinal studies (Guerry & Prinstein, 2010;Hankin & Abela, 2011;Wilcox, Arria, Caldeira, Vincent, Pinchevsky, & O'Grady, 2012). Furthermore, You and Leung (2012) reported that behavioral impulsivity at baseline contributed to both the occurrence and recurrence of NSSI two years later, whereas depressive symptoms failed to predict NSSI frequency.…”
Section: Intrapersonal Correlates Of Nssimentioning
confidence: 97%
“…In addition to the NSSI models, it is noteworthy that 10-37% of individuals who engage in NSSI also engage in suicidal behaviors (e.g., Andover, Primack, Gibb, & Pepper, 2010; Asarnow et al, 2011;Glenn & Klonsky, 2009;Wilcox et al, 2011). Current NSSI engagement and current number of methods used have been showm to be the strongest predictors of suicidal ideations (Wester et al, in press), joiner (2005) posited that acquired ability for lethal self-harm must exist; thus, NSSI behaviors can desensitize an individual to lethal means of self-harm, particularly when combined with thwarted belonging (i.e., isolation) and perceived burdensomeness on others.…”
Section: Articlementioning
confidence: 99%
“…While empirical support has been found for various components of the conceptual models of NSSI, rarely has the model been explored in its entirety, and less commonly have the voices of individuals who self-injure been heard in relation to these models. These voices are needed to further validate conceptual NSSI models and to explore if there are additional pathways or factors that should be added to the existing frameworks of NSSI.In addition to the NSSI models, it is noteworthy that 10-37% of individuals who engage in NSSI also engage in suicidal behaviors (e.g., Andover, Primack, Gibb, & Pepper, 2010; Asarnow et al, 2011;Glenn & Klonsky, 2009;Wilcox et al, 2011). Current NSSI engagement and current number of methods used have been showm to be the strongest predictors of suicidal ideations (Wester et al, in press), joiner (2005) posited that acquired ability for lethal self-harm must exist; thus, NSSI behaviors can desensitize an individual to lethal means of self-harm, particularly when combined with thwarted belonging (i.e., isolation) and perceived burdensomeness on others.…”
mentioning
confidence: 99%
“…El hecho de que el estudiante universitario perciba que dispone de amigos y familiares que promueven actitudes positivas (de escucha, afecto y apoyo), sobre todo durante las primeras fases de ideación suicida, produce un efecto positivo directo de carácter protector contra una futura tentativa suicida (Wilcox et al, 2012).…”
Section: Introductionunclassified